2021
DOI: 10.3390/nu13051681
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Renal Clearance Following Traumatic Injury in Critically Ill Patients Requiring Nutrition Therapy

Abstract: The intent of this study was to ascertain the prevalence of augmented renal clearance (ARC) in patients with traumatic injuries who require nutrition therapy and identify factors associated with ARC. Adult patients admitted to the trauma intensive care unit from January 2015 to September 2016 who received enteral or parenteral nutrition therapy and had a 24 h urine collection within 4 to 14 days after injury were retrospectively evaluated. Patients with a serum creatinine concentration > 1.5 mg/dL, required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…Patients with higher protein intakes were characterized by higher levels of CRCL, without statistical difference regarding ∆CSA and %∆CSA compared to patients who received low protein intakes. These results are in accordance with a recent study suggesting a worsened nitrogen balance (−10.8 ± 13.0 vs. −6.2 ± 9.2 g/day, p = 0.004) in critically ill patients with ARC, although this study was impaired by the lack of muscle mass measurements and longitudinal data (only the first measurement being used for analysis) [5]. Of note, the authors also found a significant association between ARC and increased protein intake (adjusted OR: 2.06 [1.09, 3.91]).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients with higher protein intakes were characterized by higher levels of CRCL, without statistical difference regarding ∆CSA and %∆CSA compared to patients who received low protein intakes. These results are in accordance with a recent study suggesting a worsened nitrogen balance (−10.8 ± 13.0 vs. −6.2 ± 9.2 g/day, p = 0.004) in critically ill patients with ARC, although this study was impaired by the lack of muscle mass measurements and longitudinal data (only the first measurement being used for analysis) [5]. Of note, the authors also found a significant association between ARC and increased protein intake (adjusted OR: 2.06 [1.09, 3.91]).…”
Section: Discussionsupporting
confidence: 93%
“…Early targeted protein intake is thought to improve short-term outcome, reduce muscle wasting and hospital mortality [2,3]. Despite several limitations, determination of nitrogen balance is one of the most common methods to assess muscle catabolism and determine the targeted protein requirement [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…We found that ARC occurred relatively early after ICU admission, which is opposed to the findings of Beunders et al, who found that ARC occurred late on median (IQR) day 28 (21–42) following ICU admission during COVID-19 infections [ 17 ], but is in line with the findings of previous studies in general ICU patients (the highest ARC prevalence was observed on day 5) and critically ill COVID-19 patients (the median (IQR) first day of ARC was day 2 (3–5) of ICU stay) [ 1 , 19 ]. Next, age was ranked as the third most important feature, which was expected since age has consistently shown a significant inverse association with ARC in many studies [ 7 , 9 , 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Age might be more relevant in this patient population since it has been noticed that some COVID-19 variants are more prevalent in young patients [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 95%
“…In critically ill patients, prevalence of ARC usually ranges from 20% to 65% 1,3–5,7,9,11–14,20,22–27 . Higher prevalence has been reported in specific groups of patients such as traumatic brain injury (TBI) (85%) 28 and subarachnoid haemorrhage (100%) 29 .…”
Section: What Is Knownmentioning
confidence: 99%
“…4,7,12,22 In critically ill patients, prevalence of ARC usually ranges from 20% to 65%. 1,[3][4][5]7,9,[11][12][13][14]20,[22][23][24][25][26][27] Higher prevalence has been reported in specific groups of patients such as traumatic brain injury (TBI) (85%) 28 and subarachnoid haemorrhage (100%). 29 Several risk factors of ARC have been identified such as younger age, male sex, trauma and lower severity of illness expressed by the Sequential Organ Failure Assessment (SOFA) score or the Acute Physiologic Assessment and Chronic Health Evaluation II (APACHE II) score.…”
mentioning
confidence: 99%